Landslide аnd Landslide-Talus Processes оn the Highways оf the Republic оf Ingushetia - V. V. Razumov; M. Ch. Zalikhanov; N. D. Bogdanova; N. V. Razumova (Наука. Инновации. Технологии)
Introduction. A significant impact on the geological environment of the Republic of Ingushetia and the development of dangerous slope processes is exerted by the construction, reconstruction and operation of highways, which make significant changes to the natural environment of mountain slopes. The article provides an assessment of the degree of activity and danger of landslide and landslide-talus processes on the highways of the republic for 2005–2022.Materials and research methods. The key method used in this work was the analysis of various materials containing information on the activity of the manifestation of landslide and avalanche-talus processes on the highways of the Republic of Ingushetia. The main sources used were literary sources, reports and published data of the Center for State Monitoring of the State of the Subsoil (GMSN) of the Federal State Budgetary Institution «Hydrospetsgeology» for 2005–2022.Research results and their discussion. The authors characterized the conditions and causes, as well as assessed the activity and danger of landslide and landslide-talus manifestations on the highways of the Republic of Ingushetia for 2005–2022. The paper provides information on the extent of the destruction and deformation of the roadway.Conclusions. The analysis of the activity of landslide manifestations on the roads of the Republic of Ingushetia over the past 18 years has shown that the greatest extent of landslide activity was observed in 2010, 2016 and 2017, and a very weak degree of activity was observed in 2008. The maximum landslide activity on the roads of the republic was observed in 2005 and 2013, and the minimum – in 2019. According to the results of the study, the sections of the republic’s highways that are most susceptible to landslide and landslide-talus processes have been identified. The performed analysis indicates the predominant development of landslide manifestations on the roads of the Malgobek administrative district, and landslide-talus – on the roads of the Jeyrakh district.